Looking through the Lenses of Educational Management Information Systems (EMIS) - Aheto, S.-P.K.; Fletcher, J. (International Journal of Computing Academic Research (IJCAR), 2012)
The study examined the user awareness and use of Educational Management Information Systems (EMIS) by educational stakeholders, e.g. educators, parents, guardians, students, educational NGOs and consultants and the public in the Greater Accra Region in Ghana. The descriptive research design was used for the study. Purposive sampling technique was employed in selecting the sample for the study. The coverage area for the study was the Greater Accra Regional Education Office, two other municipal and one metropolitan Education Office. The study sample size was 48 which included the Regional/ Metropolitan/ Municipal Directors of Education with their four Frontline Assistant Directors. Others that were included in the sample were EMIS Co-ordinators, EMIS officers, Circuit supervisors, Heads of Primary, Junior and Senior High Schools and Teachers. The instrument used for data collection was self prepared. In all, there were three research questions which were all captured by the instrument for data collection. The study revealed that: EMIS offices are present in the Regional and District Education Offices included in the sample in the Greater Accra Region; there is user awareness among educational stakeholders identified in the study, the core objectives of EMIS are being met; Ministry of Education sees the Annual School Census as the most important source of information regarding the situation of every school. It was further found that EMIS has no dedicated website. Also, EMIS users are usually those who are aware of its existence, hence awareness of EMIS informs its utilisation. Parents are rare users of EMIS. The study recommended that EMIS should have a dedicated and reliable website where users, patrons, researchers and stakeholders could rely on for educational information.
Keywords: Awareness; EMIS; Lens; Utilisation